Very-late-onset neuromyelitis optica spectrum disorder: a case report and review - Liu, Rui-Ting; Guo, Yu-Kun; Du, Xia; Li, Heng (Frontiers in Neurology, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disorder that causes demyelination within the central nervous system, typically manifesting as symptoms of optic neuritis and myelitis. We report the case of a 92-year-old patient with NMOSD who was admitted to our hospital; hers is currently the oldest reported case of NMOSD globally. The onset occurred after COVID-19 vaccination, and the patient responded well to treatment with satralizumab.